La persistencia de la segregación residencial socioeconómica en Argentina - Groisman, Fernando (El Colegio de México A.C., 2010)
This document explores one of the aspects of the dynamics of socio-economic regional segregation: its persistence over time. The topic is analyzed in the context of the economic recovery undergone by Argentina after the 2001 crisis. This period saw a sharp drop in poverty and unemployment, while there was a decrease in income distribution inequality improved in the early years before leveling off. Fictitious cohorts are used to assess whether those in environments exposed to higher levels of socio-economic deprival improved their situation in relative terms during this period. The results obtained suggest that the pattern of socio-economic residential segregation was not modified. This forces one to advance towards the discussion of a public policy agenda that will specifically take into account these aspects of the population’s welfare.